THE INFLUENCE OF CONFUCIAN IDEALS ON POLITICAL LEADERSHIP AND INSTITUTIONAL PRACTICES IN SOUTH KOREA AND JAPAN - Aldabek, N.A.; Ashinova, Zh.Ye.; Belyalova, A.E. (Journal of Oriental Studies, 2025)
Confucianism, with its philosophical principles and historical significance, has played a crucial role in shaping the sociopolitical landscapes of East Asia, particularly in Korea and Japan. Originating in China, Confucian ideals emphasize moral virtue, social order, and hierarchical structures, influencing various aspects of society. This study focuses on the lasting impact of Confucianism on political leadership and institutional practices in both countries, analyzing how these values have been integrated and adapted within their governance systems. In Korea, Confucianism served as the foundation of governance during the Joseon Dynasty, contributing to the development of a bureaucratic state rooted in Neo-Confucian thought. In Japan, Confucian principles were incorporated alongside Shinto and Buddhist traditions, creating a distinct political culture that emphasizes meritocratic leadership and hierarchical order. The research utilizes a qualitative approach, drawing on historical documents, scholarly articles, and governmental resources to examine the ongoing influence of Confucian values. By comparing the political structures and leadership styles of both countries, the study aims to identify similarities and differences in their application of Confucian ideals. The findings are expected to contribute to academic discussions on the integration of cultural values in political systems, providing valuable insights for policymakers and scholars. Understanding these traditions can inform the development of culturally sensitive governance strategies, fostering more harmonious and contextually relevant political frameworks in East Asia and beyond. Keywords: confucianism, political leadership, institutional practices, historical influence, South Korea, Japan